Efecto de técnicas y sistemas de protección en la injertación de sacha inchi (plukenetia volubilis l.), bajo condiciones de vivero en San Martín - Hidalgo Ganoza, Leonardo Miles Davis (2009)
In the present experiment the effects of three techniques of grafting and three security systems on the ignition and growth of the graft in Sacha Inchi (Plukenetia volubilis L.). The trial was conducted in the nursery of the Instituto de Investigaciones de la Amazonía Peruana in San Martin; design using a randomized complete block with 3x3 factorial arrangement formed by nine treatments, four repetitions and experimental units of ten grafted plants. At the end of 45 days was a percentage of ignition of 100%, with barbed central, double tongue and splice protected with moist chamber. The technique of grafting is not influenced significantly, but showed better performances in central stinger. We conclude that it is possible graft sacha inchi using the technique of plectrum and the central system for protecting plastic bag under nursery conditions.